Shaping The Image of Muslim Women in Buttonscarves Advertisement: A Multimodal Discourse Analysis - Ul'ya, Nelly Yulfa; Kurniawan, Muhammad Hafiz (Universitas Muhammadiyah Mataram, 2025)
This study examines the multimodal construction of Muslim women's image in Buttonscarves ads, drawing on both verbal and visual components. Four official Buttonscarves campaign videos comprise the study data. The verbal mode was examined using Halliday's (2014) Systemic Functional Linguistics theory, while the visual mode was investigated using Machin & Mayr's (2012) Multimodal Critical Discourse Analysis method. While the verbal analysis addressed mood, modality, polarity, temporal deixis, and speech function, the visual analysis concentrated on salience, color, attributes, background, size, and tone. The findings demonstrate how the hijab and the figures of women are visually portrayed through aspirational metropolitan settings, warm, vibrant colors, upscale, high salience, and semi-formal apparel attributes. Modern Muslim women are portrayed as elegant, independent, professional, and of high social standing. In verbal communication, the prevalence of declarative mood, positive polarity, and the absence of imperative and interrogative forms suggest an affirmative communication style that does not allow for compromise. This multimodal result demonstrates the existence of a consumerist ideology of femininity grounded in contemporary religion, which frames the hijab as a sign of social class, lifestyle, and contemporary goals in addition to being a symbol of piety. Aspirational capitalism, spiritual capitalism, and religious postfeminism are all reflected in this portrayal, where empowerment is determined by style, consumerism, and visual performativity in accordance with market principles. According to this study, Buttonscarves' commercials not only offer goods but also create an ideology that balances consumerism, modernity, and spirituality in the representation of modern Muslim women. This article contributes to multimodal critical discourse analysis by integrating MCDA and systemic functional linguistics to demonstrate how verbal and visual modes interact to construct ideological meanings in premium hijab advertising. This domain remains largely underexamined in contemporary discourse studies.